Development of transparent microwell arrays for optical monitoring and dissection of microbial communities - Halsted, M.; Wilmoth, J. L.; Briggs, P. A.; Hansen, Ryan R.; Briggs, D. P.; Timm, A. C.; Retterer, S. T. (My University, 2016)
Microbial communities are incredibly complex systems that dramatically and ubiquitously influence our lives. They help to shape our climate and environment, impact agriculture, drive business, and have a tremendous bearing on healthcare and physical security. Spatial confinement, as well as local variations in physical and chemical properties, affects development and interactions within microbial communities that occupy critical niches in the environment. Recent work has demonstrated the use of silicon based microwell arrays, combined with parylene lift-off techniques, to perform both deterministic and stochastic assembly of microbial communities en masse, enabling the high-throughput screening of microbial communities for their response to growth in confined environments under different conditions. The implementation of a transparent microwell array platform can expand and improve the imaging modalities that can be used to characterize these assembled communities. Here, the fabrication and characterization of a next generation transparent microwell array is described. The transparent arrays, comprised of SU-8 patterned on a glass coverslip, retain the ability to use parylene lift-off by integrating a low temperature atomic layer deposition of silicon dioxide into the fabrication process. This silicon dioxide layer prevents adhesion of the parylene material to the patterned SU-8, facilitating dry lift-off, and maintaining the ability to easily assemble microbial communities within the microwells. These transparent microwell arrays can screen numerous community compositions using continuous, high resolution, imaging. The utility of the design was successfully demonstrated through the stochastic seeding and imaging of green fluorescent protein expressing Escherichia coli using both fluorescence and brightfield microscopies. (C) 2016 American Vacuum Society.
Citation: Halsted, M., Wilmoth, J. L., Briggs, P. A., Hansen, R. R., Briggs, D. P., Timm, A. C., & Retterer, S. T. (2016). Development of transparent microwell arrays for optical monitoring and dissection of microbial communities. Journal of Vacuum Science & Technology B, 34(6), 5. doi:10.1116/1.4962739
Keywords: Lift-Off; Microfluidics; Engineering; Science & Technology - Other Topics; Physics